2009
DOI: 10.1007/s11904-009-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection of the genital mucosa in women

Abstract: The vast majority of new HIV infections are acquired via the genital and rectal mucosa. Here, we provide an overview of our current knowledge of how HIV establishes local infection, with an emphasis on viral invasion through the female genital tract. Studies using human explant tissues and in vivo animal studies have improved our understanding of the cellular and molecular pathways of infection; this information could be harnessed to design effective HIV vaccines and microbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 59 publications
2
152
0
1
Order By: Relevance
“…It encounters multiple barriers to successful transmission (15) as it migrates through highly compartmentalized mucosal tissues. Moreover, it has been suggested that dendritic cells facilitate this migration (15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It encounters multiple barriers to successful transmission (15) as it migrates through highly compartmentalized mucosal tissues. Moreover, it has been suggested that dendritic cells facilitate this migration (15).…”
Section: Resultsmentioning
confidence: 99%
“…It encounters multiple barriers to successful transmission (15) as it migrates through highly compartmentalized mucosal tissues. Moreover, it has been suggested that dendritic cells facilitate this migration (15). Neither the biopsies that we analyzed nor our culture systems reflect this complexity; however, the capacity of ␣ 4 ␤ 7 to capture HIV-1 virions (9) suggests that it can facilitate infection of activated cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra-epithelial processes of the LCs help convey HIV to the submucosal lymphocytes, and following productive infection of these CD4 + T cell populations; the virus is able to propagate and disseminate via lymphatic mechanisms. 31,32 Studies from non-human primates suggest that SIV penetrates the cervicovaginal epithelium and is able to infect a small population of cells within an hour. 30,33 Recently, human cervical explant and in vivo macaque exposure studies using photoactivatable-labeled virions have shown that HIV-1 can readily penetrate both intact columnar and squamous epithelium; however, the cervicovaginal epithelium is highly susceptible to viral infiltration via 'diffusive percolation' through interstitial spaces, while HIV-1 entry is impeded at the endocervical epithelium by mucus production.…”
Section: Mechanism Of Sexual Transmission Of Hivmentioning
confidence: 99%
“…74,86,87 LCs, present in cervicovaginal mucosa, are among the primary targets of HIV-1/SIV. 30,31,88,89 LCs are able to capture HIV-1 virions and transport them to the draining lymph nodes where the virions can be transmitted to T cells for productive infection, 27,[88][89][90] although there is some evidence to suggest viral particles captured by LCs are internalized and rendered incapable of infection. 90 In women, semen-enhanced infiltration of LCs into the genital epithelium has been demonstrated.…”
Section: Seminal Plasma and Female Genital Tract Immune Responsementioning
confidence: 99%